Psychometric Study of the Social Responsiveness Scale in Phelan–McDermid Syndrome - Gergoudis, Kellie (Autism Res, 2020)
The Social Responsiveness Scale-2 (SRS-2) is a quantitative measure used to characterize symptoms of autism spectrum disorder (ASD). However, research suggests that SRS-2 scores are significantly influenced by language ability and intellectual disability (ID). Efforts to refine the SRS-2 by Sturm, Kuhfeld, Kasari, and Mccracken [Journal of Child Psychology and Psychiatry, 58(9), 1053–1061] yielded a shortened form, yet its psychometric properties in populations with severe ID remain unknown. This study aims to examine the psychometric properties of the SRS-2 in Phelan–McDermid syndrome (PMS), a genetic condition associated with ASD and ID, thereby guiding score interpretation in this population and future development of targeted scales. Analyses, including Item Response Theory (IRT), were conducted on a sample of individuals with PMS (n = 91) recruited at six sites nationally. Psychometric properties evaluated include measures of reliability (internal consistency, test–retest reliability) and validity (structural, construct, content). While both SRS-2 forms are reliable, the shortened SRS-2 shows superior validity to the full SRS-2 for measuring ASD symptoms in PMS. On IRT analysis, the shortened SRS-2 shows excellent discrimination and precisely evaluates respondents across a wide range of ASD symptomatology but interpretation is limited by uncertain content validity and small sample size. The shortened SRS-2 shows some promise for use in PMS, but future refinements and additions are needed to develop items that are tailored to identify ASD in children with severe ID and specifically PMS.